Osteoporosis in Cirrhotic Patients - Selda Sarıkaya; Özgür Ortancıl; Yücel Üstündağ; Ülkü Koç; Aynur Başaran (Archives of Rheumatology, 2006)
Objective: The aim of this study was to determine the osteoporosis at different sites in cirrhotic patients and relation of osteoporosis with duration and severity of disease. Patients and Methods: Twenty-eight patients (13 women, 15 men) with cirrhosis were included in this study. Dual-energy X-ray absorptiometry ( DEXA) was used to measure the bone mineral densities (BMD) of the lumbar spine (L1-L4), left femur (total) and forearm. The severity of cirrhosis was graded using the Child-Pugh score. Results: Osteoporosis at lumbar spine was found in 23.1% of female and 46.7% of male patients while 23.1% of females and 20% of males had osteoporosis at femur. According to forearm BMD measurements, 33% of women and 50% of men had osteoporosis. There were no significant differences between Child-Pugh class A, B and C in BMD and Z scores (p>0.05). We found no statistically significant correlation between disease duration and spine (r=-0.053, p=0.790), femur(r=0.302, p=0.119) and forearm (r=-0.236, p=0.303) Z scores. There were no statistically significant correlation between disease duration and spine (r=-0.071, p=0.721)and femur (r=0.090, p=0.650 T scores while there was a statistically significant negative correlation between disease duration and forearm T score (r=-0.486; p=0.025). Conclusion: One of two cirrhotic patients has osteoporosis in our study. Cirrhotic patients have sedantery lives due to their diseases. Osteoporotic fractures increase the duration and grade of immobilisation and diminish quality of patients lives. For this reason cirrhotic patients should be evaluated for osteoporosis thus the number of subsequent fractures may be decreased by early diagnose and intervention. (Rheumatism 2006; 21: 37-40)